Muscle recruitment during plyometric exercises in overhead athletes with and without shoulder pain. (May 2020) - Werin, Maria; Maenhout, Annelies; Smet, Stephanie; Van Holder, Laura; Cools, Ann
Abstract: Objectives: To investigate if there is a difference in muscle activity patterns during high load plyometric shoulder exercises between overhead athletes with and without shoulder pain. Design: Controlled laboratory EMG study. Setting: University EMG Laboratory. Participants: Sixty overhead athletes, 30 with shoulder pain and 30 healthy controls were included. Main outcome measures: The EMG activity of Upper Trapezius (UT), Middle Trapezius (MT), Lower Trapezius (LT), Serratus Anterior (SA), Latissimus Dorsi (LD) and Pectoralis Major (PM) on the tested side and bilateral on Abdominal Obliques Externus (OE) muscles was registered with wireless surface EMG during 3 rotational plyometric shoulder exercises in 3 positions, prone, sidelying and standing. Results: A significant higher muscle activity was found in the shoulder pain group for MT together with an overall significant higher activity in the thoraco-humeral and abdominal muscles compared to healthy controls. Conclusions: When rehabilitating the overhead athlete with shoulder pain, shoulder muscles together with both thoraco-humeral and abdominal muscles need to be engaged. Highlights: Overhead athletes with shoulder pain had higher muscle activity in the thoraco-humeral muscles, Pectoralis Major and Latissimus Dorsi, than healthy controls during plyometric rotational exercises. Even though, not challenging the kinetic chain, overhead athletes with shoulder pain had higher muscle activity in the External Obliques muscles during the shoulder rotational exercises. The shoulder pain group had higher activity in Middle Trapezius in prone position compared to healthy controls. Training of the scapular muscles in isolation and in the kinetic chain are important treatment goals in the rehabilitation of an overhead athlete with shoulder problems.